Gut Microbiota in Acute Ischemic Stroke: From Pathophysiology to Therapeutic Implications - Battaglini, Denise; Pimentel-Coelho, Pedro Moreno; Robba, Chiara; dos Santos, Claudia C.; Cruz, Fernanda Ferreira; Pelosi, Paolo; Rocco, Patricia Rieken Macedo (Frontiers in Neurology, 2020)
The microbiota–gut–brain axis is considered a central regulator of the immune system after acute ischemic stroke (AIS), with a potential role in determining outcome. Several pathways are involved in the evolution of gut microbiota dysbiosis after AIS. Brain–gut and gut–brain signaling pathways involve bidirectional communication between the hypothalamic–pituitary–adrenal axis, the autonomic nervous system, the enteric nervous system, and the immune cells of the gut. Alterations in gut microbiome can be a risk factor and may also lead to AIS. Both risk factors for AIS and gut-microbiome composition are influenced by similar factors, including diabetes, hypertension, hyperlipidemia, obesity, and vascular dysfunction. Furthermore, the systemic inflammatory response after AIS may yield liver, renal, respiratory, gastrointestinal, and cardiovascular impairment, including the multiple organ dysfunction syndrome. This review focus on biochemical, immunological, and neuroanatomical modulation of gut microbiota and its possible systemic harmful effects after AIS, as well as the role of ischemic stroke on microbiota composition. Finally, we highlight the role of gut microbiota as a potential novel therapeutic target in acute ischemic stroke.